2009
DOI: 10.1351/pac-con-08-08-25
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a bowl-type dodecavanadate by the coupling reaction of alkoxohexavanadate and discovery of a chiral octadecavanadate

Abstract: )] 5-, in both the solid and solution states through extended X-ray absorption fine structure (EXAFS) studies. The existence of the chiral inorganic species in acetonitrile with double-stranded V8 chains was confirmed through EXAFS oscillations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This serves to diminish the charge, and a reducing state of V IV is preferred by the introduction of alkoxide ligands [83]. The substitution of all bridging oxygens with CH 3 O - [84,85] [98]. This straightforward synthesis of alkoxides provides a facile route for further development of polyoxovandate synthesis.…”
Section: Alkoxohexavanadatesmentioning
confidence: 99%
“…This serves to diminish the charge, and a reducing state of V IV is preferred by the introduction of alkoxide ligands [83]. The substitution of all bridging oxygens with CH 3 O - [84,85] [98]. This straightforward synthesis of alkoxides provides a facile route for further development of polyoxovandate synthesis.…”
Section: Alkoxohexavanadatesmentioning
confidence: 99%
“…Therefore, this study opens new avenues for the design, development and application of chiral inorganic photocatalysts. , was reported by Hayashi et al 22 In addition, several vanadate-based polymeric helices have been reported, most notably an enantiomerically pure, helical coordination polymer discovered by Zubieta et al…”
mentioning
confidence: 91%
“…1 and ESI †) are observed in a 1 : 1 ratio so that 1 crystallizes as a racemate. To the best of our knowledge, this is only the second example of a non-polymeric chiral vanadium oxide cluster and the first example of a heterometallic chiral polyoxovanadate: in 2009, the first chiral polyoxovanadate, [V 18 O 46 (NO 3 )] 5À , was reported by Hayashi et al 22 In addition, several vanadate-based polymeric helices have been reported, most notably an enantiomerically pure, helical coordination polymer discovered by Zubieta et al 23 It should be noted that the chirality of 1a is not helical chirality 23 nor distortion chirality 7 (chirality caused by alternating bond lengths) which are two common chirality modes observed in POMs. 7,8 Instead, the chirality in 1a is a consequence of the C 2 -symmetry and the non-planar, convex structure of the {V 4 } building blocks (inherent chirality).…”
mentioning
confidence: 93%
“…The structure of the cyclic inorganic framework may be less rigid than that of the spherical structures. [14] The structural fluctuation may be the cause of the weak intensities of the peaks in the range 2-4 Å, and the larger Debye-Waller factor. The fitted data exhibits similar V···V lengths in 1 and 2 and indicates that both complexes are composed of cyclic structures based on the linkages of the VO 4 tetrahedra.…”
Section: Structuresmentioning
confidence: 99%